The high energy X-ray probe (HEX-P): Resolving the nature of Sgr A* flares, compact object binaries and diffuse X-ray emission in the Galactic center and beyond - Mori, Kaya; Ponti, Gabriele; Bachetti, Matteo; Bodaghee, Arash; Grindlay, Jonathan; Hong, Jaesub; Krivonos, Roman; Kuznetsova, Ekaterina; Mandel, Shifra; Rodriguez, Antonio; Stel, Giovanni; Zhang, Shuo; et al. (Frontiers in Astronomy and Space Sciences, 2024)
HEX-P is a probe-class mission concept that will combine high spatial resolution X-ray imaging (< 10 ′′ FWHM) and broad spectral coverage (0.2-80 keV) with an effective area far superior to current facilities' (including XMM-Newton and NuSTAR). These capabilities will enable revolutionary new insights into a variety of important astrophysical problems. We present scientific objectives and simulations of HEX-P observations of the Galactic Center (GC) and Bulge. We demonstrate the unique and powerful capabilities of the HEX-P observatory for studying both X-ray point sources and diffuse X-ray emission. HEX-P will be uniquely equipped to explorea variety of major topics in Galactic astrophysics, allowing us to (1) investigate broad-band properties of X-ray flares emitted from the supermassive black hole (BH) at Sgr A* and probe the associated particle acceleration and emission mechanisms; (2) identify hard X-ray sources detected by NuSTAR and determine X-ray point source populations in different regions and luminosity ranges; (3) determine the distribution of compact object binaries in the nuclear star cluster and the composition of the Galactic Ridge X-ray emission; (4) identify X-ray transients and measure fundamental parameters such as BH spin; (5) find hidden pulsars in the GC; (6) search for BH-OB binaries and hard X-ray flares from young stellar objects in young massive clusters; (7) measure white dwarf (WD) masses of magnetic CVs to deepen our understanding of CV evolution and the origin of WD magnetic fields; (8) explore primary particle accelerators in the GC in synergy with future TeV and neutrino observatories; (9) map out cosmic-ray distributions by observing non-thermal X-ray filaments; (10) explore past X-ray outbursts from Sgr A* through X-ray reflection components from giant molecular clouds.